On the Development of Evaluation Systems in Latin America and the Caribbean - Feinstein, Osvaldo Néstor (Revista del CLAD Reforma y Democracia, 2015)
Important advances have been made, but there is still a long road to travel and this article attempts to provide guidelines to contribute to the strengthening of evaluation systems in the region. The challenges, questions and proposals identified in the document focus the attention on those issues that are fundamental to promote a suitable development of evaluation systems, so that they can play a role in improving public administration in the Latin American and Caribbean countries.The paper makes the following proposals: to delink monitoring from evaluation systems; to use a matrix that allows to take into account demands and supplies of evaluation from different agents and principals, avoiding an “aggregated” approach to evaluation supply and demand; to identify critical success factors in the development of evaluation systems, linking them to the implementation context suitable for their application, using the abundant number of studies on evaluation systems, particularly but not only in LAC, as a source of inspiration, but not to merely copy them without adaptation.
Keywords: Evaluation; Evaluation Systems; Latin America; Caribbean